Characterization and distribution of novel alleles of the vernalization gene Vrn-A1 in Chinese wheat (Triticum aestivum L.) cultivars - Bo Zhang; Yangyang Guo; Qiru Fan; Ruibo Li; Dongsheng Chen; Xiaoke Zhang (Crop Journal, 2023)
The ability of wheat to adapt to a wide range of environmental conditions is determined mostly by allelic diversity among genes regulating vernalization requirement. Vrn-1 is a major regulator of this requirement. In this study, two novel alleles of Vrn-A1 were discovered in Chinese cultivars: vrn-A1n was identified in two landraces, Jiunong 2 and Ganchun 16, and Vrn-A1o was detected in Duanhongmangmai. Both novel alleles showed a linked duplication in the promoter region. The common copy of these two alleles was identical to the recessive allele vrn-A1. Compared with the recessive allele vrn-A1, the other copy of vrn-A1n contained a 54-bp deletion in the promoter region and the distinct copy of Vrn-A1o contained an 11-bp deletion in the promoter region. In segregating populations in the greenhouse under nonvernalizing (20–25 °C) and long-day (16 h light) conditions, plants with the novel vrn-A1n allele did not head earlier than those with the recessive vrn-A1 allele. However, plants that were either homozygous or heterozygous for the novel Vrn-A1o allele headed earlier than those with the recessive vrn-A1 allele. To identify the novel allele with the small-sized product and facilitate screening, a DNA marker for the novel dominant allele Vrn-A1o was designed. Analysis of the novel-allele distribution showed that two cultivars carrying the vrn-A1n allele were dispersed in the northwestern spring wheat zone, and 12 cultivars carrying the dominant Vrn-A1o allele were widely distributed in the northwestern spring wheat zone, Xinjiang winter and spring wheat zone, Yellow and Huai River valley winter wheat zone, and Qinghai-Tibetan Plateau spring and winter wheat zone. Our study identifies useful germplasm and a DNA marker for wheat breeding.